Nearly Half of Women Have Experienced Intimate Partner Violence During Pregnancy in Northwest Ethiopia, 2021; The Role of Social Support and Decision-Making Power - Azmeraw Ambachew Kebede; Mastewal Belayneh Aklil; Dereje Nibret Gessesse; Nuhamin Tesfa Tsega; Wubedle Zelalem Temesgan; Marta Yimam Abegaz; Tazeb Alemu Anteneh; Nebiyu Solomon Tibebu; Haymanot Nigatu Alemu; Tsion Tadesse Haile; Asmra Tesfahun Seyoum; Agumas Eskezia Tiguh; et al. (Frontiers Media S.A., 2022)
BackgroundIn developing countries, intimate partner violence is increasing alarmingly, though attention to this issue is rarely given. It has devastating effects on the general wellbeing of women, pregnancy outcomes, and the long-term health of children, and this needs to be addressed. Hence, this study was designed to assess intimate partner violence and associated factors in northwest Ethiopia.MethodsA community-based cross-sectional study was conducted from July 1st to August 30th, 2021, among 858 postpartum women in Gondar city. A cluster sampling technique was employed to select the study participants. EPI DATA version 4.6 and SPSS 25 were used for data entry, cleaning and analysis, respectively. A bivariable and multivariable logistic regression model was fitted to identify factors associated with intimate partner violence. The level of significant association was declared using the adjusted odds ratio (AOR) with 95 % confidence interval (CI) and a p-value of ≤ 0.05.ResultsIn this study, 48.6% of women indicated having experienced intimate partner violence during pregnancy (95% CI: 45.3, 51.7). The odds of intimate partner violence during pregnancy were significantly higher among women who were not able to read and write (AOR = 4.96; 95% CI: 2.15, 11.41), were private workers (AOR = 1.78; 95% CI: 1.05, 3.02), and had low decision-making power (AOR = 1.43; 95% CI: 1.06, 1.95), a poor social support (AOR = 1.99; 95% CI: 1.32, 3.02), and unsupported pregnancy by family (AOR = 2.32; 95% CI: 1.26, 4.24). Whereas a family size of ≥ 5 (AOR = 0.73; 95% CI: 0.54, 0.98) appeared to be a protective factor for intimate partner violence.ConclusionThe magnitude of intimate partner violence was unacceptably high in the study area and connected to poor women's empowerment and social determinants of health. Thus, it is important to focus on interventions that improve women's access to social support and allow them to participate in all aspects of household decision-making through community-based structures and networks. It is also important to encourage women to improve their educational status and arrange risk-free employment opportunities.